A review of the soldier flies (Diptera: Stratiomyidae) of Sardinia - Mason, Franco; Rozkošný, Rudolf; Hauser, Martin (Zootaxa, 2009)
All published records on Stratiomyidae from Sardinia were critically evaluated and extensive, recently collected material (more than 500 specimens) was identified. The present review of the soldier flies from Sardinia includes 27 species. Nemotelus niloticus Olivier, 1811 is newly recorded from Europe and Italy, and Lasiopa pseudovillosa Rozkošný, 1983 and Zabrachia tenella (Jaennicke, 1866) are newly recorded from Sardinia. Nemotelus brachystomus Loew, 1846 and N. leucorhynchus Costa, 1884 are proposed as new synonyms of N. notatus Zetterstedt, 1842. Beris hyaliniventris Costa, 1857, the types of which could not be found, is removed from synonymy with Chorisops tibialis (Meigen, 1820) and declared as species incertae sedis. Brief comments are made on the zoogeography of Sardinian soldier flies.